Impact of Bundled Payment Care Improvement Initiative on Health Care Expenditure in Major Bowel Procedures. Issue 6 (3rd May 2022) - Goldstone, Robert N.; Zhang, Jianying; Stafford, Caitlin; Bordeianou, Liliana; Kunitake, Hiroko; Cauley, Christy E.; Francone, Todd D.; Ricciardi, Rocco
Abstract : BACKGROUND: The Bundled Payments for Care Improvement initiative links payments for Medicare beneficiaries during an episode of care (90 days from index surgery). OBJECTIVE: This study aimed to determine whether major bowel participating Bundled Payments for Care Improvement organizations experience greater cost savings for colectomy while maintaining satisfactory quality outcomes compared to nonparticipating organizations. DESIGN: This is an Analysis of all Bundled Payments for Care Improvement participating hospitals for major bowel procedures (major bowel group) and propensity score–matched against Bundled Payments for Care Improvement organizations that do not include major bowel procedures (nonmajor bowel group) and those that do not participate in any Bundled Payments for Care Improvement program (non-Bundled Payments for Care Improvement group). SETTING: Programs accepting Medicare and Medicaid in the United States. PATIENTS: Patients included were major bowel cases in the Medicare Standard Analytic file within Medicare Severity Diagnosis-Related Groups 329–331 at participating facilities between January 1, 2011, and June 30, 2016. MAIN OUTCOME MEASURES: Main outcome measures included average total care expenditure and quality of care (length of stay, morbidity, and mortality) from 3 days preoperatively to 90 days postoperatively. RESULTS: We abstracted 7609 major bowel episodes from 23 major bowel group facilities, 21, 872 episodes from nonmajor bowel-matched hospitals, and 19, 383 episodes from non-Bundled Payments for Care Improvement–matched hospitals. From the baseline (January 2011 to June 2012) to final period (July 2015 to June 2016), we noted a 2955 average reduction in care expenditures. The largest decrease in average total episode expenditure occurred within the major bowel group (14% reduction) compared to the other groups (6% reduction for nonmajor bowel and 5% reduction for non-Bundled Payments for Care Improvement). Utilizing a generalized estimating equation to adjust for patient demographics, comorbidities, and hospital characteristics, the average total episode expenditure for the major bowel group decreased by 4885 (95% CI 4838–4932; p < 0.001) compared to 2050 (95% CI 2038–2061) for the non-Bundled Payments for Care Improvement group. All groups had similar reductions in length of stay, 30-day and 90-day complication rates, and readmission rates. LIMITATIONS: Analyses were limited by the retrospective nature of the study. CONCLUSIONS: Bundled Payments for Care Improvement participation for major bowel procedures resulted in a greater decrease in average total cost per episode of care than in nonparticipating hospitals without compromise in quality of care. See Video Abstract at http://links.lww.com/DCR/B837 . IMPACTO DE LA INICIATIVA BUNDLED PAYMENT AGRUPADOS PARA LA MEJORA DE LA ATENCIÓN DEL GASTO SANITARIO EN LOS PROCEDIMIENTOS INTESTINALES MAYORES ANTECEDENTES: La iniciativa de Bundled Payment para la mejora de la atención vincula los pagos para los beneficiarios de Medicare durante un episodio de atención (90 días desde la cirugía índice). OBJETIVO: Determinar si las principales organizaciones de Bundled Payment para el mejoramiento de la atención relacionados a los procedimientos intestinales experimentan mayores ahorros en los costos para una colectomía manteniendo resultados satisfactorios de calidad en comparación con las organizaciones no participantes. DISEÑO: Análisis de todos los hospitales participantes del programa Bundled Payment para la mejora de la atención para procedimientos intestinales mayores (grupo que incluyen procedimientos intestinales mayores) y puntaje de propensión comparado con las organizaciones que no incluyen dichos procedimientos (grupo que no incluye procedimientos intestinales mayores) y aquellos que no participan en ningún programa de Bundled Payment para la mejora de la atención (grupo no BPCI). MARCO: Programas que aceptan Medicare y Medicaid en los Estados Unidos. PACIENTES: Casos intestinales mayores en el archivo analítico estándar de Medicare dentro de los grupos relacionados con el diagnóstico 329–331 en los centros participantes entre el 1/1/2011–30/6/2016. PRINCIPALES MEDIDAS DE RESULTADO: Gasto total promedio y calidad de la atención (duración de la estadía, morbilidad, mortalidad) desde los 3 días preoperatorio hasta los 90 días postoperatorio. RESULTADOS: Hemos extraído 7609 episodios intestinales mayores de 23 instalaciones del grupo que incluyen procedimientos intestinales mayores, 21.872 episodios de hospitales del grupo que no incluyen procedimientos intestinales mayores y 19.383 episodios de hospitales del grupo no BPCI. Desde la línea de base (1/2011 - 6/2012) hasta el período final (7/2015 - 6/2016), notamos una reducción promedio de 2955 en los gastos de atención. La mayor disminución en el gasto promedio total por episodios ocurrió dentro del grupo que incluyen intestinales mayores (14% de reducción) en comparación con los otros grupos (6% de reducción para el grupo que no incluyen procedimientos intestinales mayores, 5% de reducción para el no BPCI). Utilizando una ecuación de estimación generalizada para ajustar los datos demográficos del paciente, las comorbilidades y las características del hospital, el gasto total promedio por episodio para el grupo que incluyen procedimientos intestinales mayores disminuyó en 4885 (IC del 95%: 4838–4932; p <0, 001) en comparación con 2050 (IC del 95%: 2038–2061) para el grupo que no pertenece al programa BPCI. Todos los grupos tuvieron reducciones similares en la duración de la estancia, tasas de complicaciones de 30/90 días y de readmisión. LIMITACIONES: Análisis limitados por la naturaleza retrospectiva del estudio. CONCLUSIONES: La participación de Bundled Payment para la mejora de la atención en aquellos procedimientos intestinales mayores resultó en una disminución mayor en el costo total promedio por episodio de atención que en los hospitales no participantes, sin comprometer la calidad de la atención. Consulte Video Resumen en http://links.lww.com/DCR/B837 . (Traducción—Dr Osvaldo Gauto )